The implementation of Integrated Quality Management System in Primary Schools of Mopani District of Limpopo Province - Mhangani, Mashawu Elisa (My University, 2011)
The purpose of this study was to look at the experiences, trainings, resources, benefits and challenges faced by schools in the implementation of the Integrated Quality Management System (IQMS) in the primary schools of the Nkowankowa Circuit at the Mopani District of Limpopo Province. As a result, the researcher was motivated to conduct a study on this topic. The scope of the research was restricted to two primary schools in the circuit. The government officials, principals, school development teams and educators had to respond to the questions asked during the interview between the researcher and the participants. Thus, the research methodology was qualitative in which a case study design was used. The sampling strategy was non-probability which led to purposive sampling to schools and participants. Data were collected through interviews, observations and documents and were analysed using the spiral steps of Creswell (2007). The findings of this study were that training was inadequate to the implementers. The support given by the Department was not enough. The resources at schools were lacking, hence little benefit by educators since IQMS started. The results showed disclosed that the majority of the participants feel that many things still have to be done for the effective implementation of IQMS, and all role players in schools need to join hands and assist one another. That is why there were lot of challenges which schools are encountering. This will give schools new shapes and performance in general will improve. Therefore, IQMS is partially implemented
Thesis (M.Ed.) -- University of Limpopo, 2012
Keywords: Quality control; School management; Education, Primary -- South Africa -- Quality control; Total quality management in education; Education, Primary -- Management; School management and organization -- South Africa